Analisis Kehidupan Rumah Tangga Dalam Film “Dua Hati Biru” Menurut Perspektif Teori Konflik Lewis A. Coser - Pramesti, Devi Oktavia (Jurnal PUBLIQUE, 2024)
This study aims to analyze the film "Dua Hati Biru" which raises the issue of the household life of young couples. This film depicts conflicts in the household that are relevant to the reality of community life. Conflicts in the film not only create social tension, but can also have a positive impact if resolved properly. Using qualitative research methods, researchers can explore in depth the conflicts of household life in the film Dua Hati Biru. A sociological literary approach is used to analyze the conflicts and integration depicted in the film's scenes, showing how conflicts affect household life while reflecting the conditions of social life in society. It is proven that as many as 58 percent of wives have conflicts with their in-laws about child care, making wives feel that their decisions are not appreciated. There is an identity crisis for couples who cannot meet the expectations of their roles and responsibilities as parents. In addition, financial instability in young couples often leads to household breakdowns, which is also one of the reasons why Generation Z is reluctant to marry. There is also toxic masculinity that is rooted in the structure of gender roles, especially among Generation Z in a patriarchal culture. This analysis refers to Lewis A. Coser's theory of conflict and integration, which is relevant to society. The study found 16 conflicts in the film Dua Hati Biru, involving husband-wife, parent-child, and in-law-in-law relationships. These conflicts are divided into 14 realistic conflicts and 2 non-realistic conflicts, reflecting the challenges of young couples such as financial problems, childcare, differences in family decisions, and parental interference. The film also shows integration through apologies and cooperation to build a family. Keywords: Two Blue Hearts Film, Conflict, Integration, Coser